PENINGKATAN KESADARAN PARTISIPASI PEMILIH PEMULA PELAJAR SMAN 34 JAKARTA PADA PEMILU SERENTAK 2024 - Syahuri, Taufiqurrohman; Hadi, Syamsul; Zaifa, Gilang Abi (Jurnal Pengabdian Masyarakat Khatulistiwa, 2023)
ABSTRACTThe participation of young voters in the democratic process is crucial in determining the future of the country. Young voters play a significant role in expressing their aspirations and voices in the democratic process. The low awareness among young voters, especially among students, poses a challenge to democracy due to the limited involvement of young people. Young individuals who meet the criteria for voting have the right to actively participate in the electoral process and express their choices. This right is constitutionally protected and forms the basis for the exercise of political rights. One of the ways to enhance the awareness of young voters and encourage their active participation in elections is through education and community engagement. This is particularly important in the context of SMAN 34 Jakarta. The goal of community engagement activities is to increase the awareness of young voters and motivate them to use their voting rights in elections. The method employed in these community engagement activities is the presentation and delivery of educational materials to the participants. During these activities, evaluations are conducted to assess the participants' understanding. The outcomes of these community engagement activities include increased awareness and understanding among young voters. This serves as a positive starting point in building a more democratic and participatory society in the electoral process.Keywords: Young Voters, Voting Rights, Democracy, StudentsABSTRAKPartisipasi pemilih pemula dalam pesta demokrasi merupakan suatu hal penting dalam penentuan masa depan negara. Pemilih pemula memiliki peranan penting dalam penyampaian aspirasi maupun suara dalam proses demokrasi. Rendahnya kesadaran pemilih pemula khusunya di kalangan pelajar menjadi hambatan demokrasi terkait minimnya partisipasi anak muda. Generasi muda yang telah memenuhi syarat sebagai pemilih memiliki hak untuk berpartisipasi menyuarakan hak pilihnya terhadap pilihannya. Ini mejadi hak yang diatur dalam konstitusi yang menjadi terselenggaranya hak politik. Salah satu cara untuk meningkatkan kesadaran pemilih pemula untuk ikut berpartisipasi aktif dalam pemilu adalah dengan dilakukannya penyuluhan atau pengabdian masyarakat terkait pentingnya partisipasi pemilih pemula di SMAN 34 Jakarta. Tujuan dilakukannya kegiatan pengabdian masyarakat adalah untuk meningkatkan kesadaran para pemilih pemula untuk ikut aktif menggunakan hak pilihnya dalam pemilu. Metode yang digunakan dalam kegiatan pengabdian masyarakat ini adalah dengan metode pemaparan atau penyampaian materi kepada peserta kegiatan. Dalam kegiatan ini juga dilakukan evaluasi terhadap para peserta guna mengukur pemahaman para peserta. Hasil dari kegiatan pengabdian masyarakat ini yaitu dapat meningkatkan pemahaman dan kesadaran para pemilih pemula. Hal ini menjadi awal yang baik untuk membangun masyarakat yang demokratis dan partisipatif dalam pemilu.Kata Kunci: Pemilih Pemula, Hak Pilih, Demokrasi, Pelajar